2016
DOI: 10.1590/0100-69912016002002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ki-67 and P16 INK4a in chemically-induced perioral squamous cell carcinomas in mice.

Abstract: Objective: to evaluate the influence of INK4a proteins immunohistochemical expressions on the clinical and morphological parameters of perioral squamous cell carcinoma induced with 9,10-dimethyl-1,2-benzanthracene (DMBA) in mice. Methods: we topically induced the lesions in the oral commissure of ten Swiss mice for 20 weeks, determining the time to tumors onset and the average tumor volume up to 26 weeks. In histopathological analysis, the variables studied were histological malignancy grade and the immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
6
2
Order By: Relevance
“…In our study, we also observed statistically significant positive linear correlations between P16 and Ki67 immunoexpression, and negative linear correlation between the membrane expression of Beta-catenin and Ki67, respectively with P16 immunoexpression. Contrary to our results, other studies showed that in carcinogenesis, tumor progression was associated with tumor proliferative fraction (Ki67-positive cells) and tumor differentiation, but without correlation with P16 expression [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we also observed statistically significant positive linear correlations between P16 and Ki67 immunoexpression, and negative linear correlation between the membrane expression of Beta-catenin and Ki67, respectively with P16 immunoexpression. Contrary to our results, other studies showed that in carcinogenesis, tumor progression was associated with tumor proliferative fraction (Ki67-positive cells) and tumor differentiation, but without correlation with P16 expression [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In the carcinogenesis model described herein, the average time for onset of lesions was 12.08 weeks, which is in contrast to a previous study where the lesions developed in 21.1 ± 2.13 weeks [23]. The plausible reason for this difference could be the weight and age of mice.…”
Section: Discussioncontrasting
confidence: 69%
“…Tongue lesion tissue samples from mice not treated with PL showed remarkable Ki-67 staining. In fact, in the 4NQO-induced oral carcinogenesis experimental model, tumor progression was associated with the proliferative fraction of the tumor (cycling cells Ki-67 positive) and tumor differentiation ( Alves et al, 2016 ) (Ref). Other studies have also shown that immunohistochemical expression of the ki-67 protein is correlated with the potential proliferation of malignant oral tumors ( Warnakulasuriya, 2010 ; Alves et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the 4NQO-induced oral carcinogenesis experimental model, tumor progression was associated with the proliferative fraction of the tumor (cycling cells Ki-67 positive) and tumor differentiation ( Alves et al, 2016 ) (Ref). Other studies have also shown that immunohistochemical expression of the ki-67 protein is correlated with the potential proliferation of malignant oral tumors ( Warnakulasuriya, 2010 ; Alves et al, 2016 ). Notably, we observed a trend towards a decrease in the survival of mice not treated with PL (data not shown), which had more severe lesions, probably caused by the weakness of these animals already at an advanced age, the toxicity of the chemical carcinogen administered, and the progressive evolution of the disease due to the absence of the phytotherapeutic that appears to inhibit the progression of more severe lesions, compared to the animals treated with PL.…”
Section: Discussionmentioning
confidence: 99%